2008
DOI: 10.1159/000182084
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Muscle Attenuation following Detraining and Retraining in Resistance-Trained Older Adults

Abstract: Background: Aging skeletal muscle is characterized not only by a reduction in size (sarcopenia) and strength but also by an increase in fatty infiltration (myosteatosis). An effective countermeasure to sarcopenia is resistance exercise; however, its effect on fatty infiltration is less clear. Objective: To examine in resistance-trained older persons whether muscle attenuation, a noninvasive measure of muscle density reflecting intramuscular lipid content, is altered with training status. Methods: Thirteen heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
164
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(181 citation statements)
references
References 68 publications
13
164
0
4
Order By: Relevance
“…Overend et al (41) described more than 20 years ago that, even though total thigh cross-sectional area is not different between young and elderly men, older men have 13 % lower total muscle plus bone area, 26 % lower quadriceps and 18 % lower hamstring area. Using computed tomography imaging, Taaffe et al (42) recently described that cessation of resistance exercise in trained older persons increases the fatty infiltration of muscle, while resumption of exercise decreases it. This effect adds to the development of mitochondrial dysfunction that is evident in the elderly and possibly a consequence of oxidative damage by reactive oxygen species (29,43) ; reduced energy production may also play a role in the development of myocyte apoptosis discussed later (44) .…”
Section: Mechanisms Of Wasting: Skeletal Musclementioning
confidence: 99%
“…Overend et al (41) described more than 20 years ago that, even though total thigh cross-sectional area is not different between young and elderly men, older men have 13 % lower total muscle plus bone area, 26 % lower quadriceps and 18 % lower hamstring area. Using computed tomography imaging, Taaffe et al (42) recently described that cessation of resistance exercise in trained older persons increases the fatty infiltration of muscle, while resumption of exercise decreases it. This effect adds to the development of mitochondrial dysfunction that is evident in the elderly and possibly a consequence of oxidative damage by reactive oxygen species (29,43) ; reduced energy production may also play a role in the development of myocyte apoptosis discussed later (44) .…”
Section: Mechanisms Of Wasting: Skeletal Musclementioning
confidence: 99%
“…This low FFM and high FM condition has been termed sarcopenic obesity. A study reported that sarcopenic obesity was associated with worse physical function than obesity or sarcopenia alone 16 , and thus it has been identified as an important cause of frailty among the elderly [17][18][19] . Thus, it may influence quality of life, although further study is required.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, changing thigh muscle and fat mass may decrease knee joint loading. Taafee et al [8] showed that high-intensity strength training significantly decreases fatty infiltration of the quadriceps in 65-to 83-year-old adults. We suggest that high-intensity strength training can impact the mechanical disease pathway to knee osteoarthritis by increasing thigh muscle function and decreasing thigh fat depots, resulting in long-term improvement in pain and function and possibly attenuate disease progression.…”
Section: Results Of Clinical Trials Investigating the Role Of Exercismentioning
confidence: 99%